The Role of Behavioral Biases with Peer Networks as a Mediating Variable in Shaping the Investment Decisions of 3rd-year BS Management Students at Ateneo de Manila University. - Jio Antonio R. Lazaro; Christopher Bagaconza; Jenny Anne H. Aurora; Bart Patrick J. Familar; Fatima Fei C. Usigan; Althea S. Villalobos (Journal of Strategic Innovation and Business Management, 2026)
This study examines the influence of behavioral biases on the investment decision- making of third-year BS Management students at Ateneo de Manila University, with peer networks as a mediating variable and weekly allowance as a moderating variable. Behavioral biases were measured in terms of loss aversion, reference dependence, probability weighting, and framing effects, while decision-making was assessed through intuitive and deliberative investment thinking, with peer networks further evaluated in terms of influence, similarity, and compatibility. Additionally, statistical tools such as frequency and percentage distribution, weighted mean, simple linear regression, and mediation and moderation analysis through regression were used for the treatment of data. The results indicate that behavioral biases have a significant influence on investment decision- making. Peer networks were found to significantly mediate the relationship between behavioral biases and investment decisions, while weekly allowance moderated this relationship only at higher allowance levels. These results highlight the need to promote financial awareness and reflective decision-making among young investors to support more responsible and deliberate investment practices.